2007
DOI: 10.1080/08958370601174990
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Consequences from Exposure to Sulfur Mustard: A Review

Abstract: Mustard gas (HD) was a widely used chemical warfare agent during World War I and more recently in the Iraq-Iran war (1980-1988). To date, dramatically, 45,000 Iranians are suffering from late respiratory complications due to MG exposure. This review covers two decades of researches on latent pulmonary effects of MG. Findings from clinical manifestations, pathologic examinations, laboratory data, lung function tests, and radiological evaluations are reviewed. From this review we are able to provide a suitable p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
100
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 160 publications
(104 citation statements)
references
References 42 publications
2
100
0
2
Order By: Relevance
“…), and better understanding these represents a challenge to optimize the therapeutic use of retinoids. [107,108] Mechanical injury + ± [1,4] Infections ± - [1] Directly associated genetic disorders -+ [3] Risk-associated gene polymorphisms + + [2] Histological features Airspace enlargement + + [1][2][3][4] Elastic fiber destruction/ disrupted assembly + + [37][38][39][40][41] Extracellular matrix remodeling + + [1][2][3][4] Diminished microvasular bed ± + [52][53][54] Dysmorphic capillary vessels + -…”
Section: Relative Inefficiency Of Retinoidsmentioning
confidence: 99%
“…), and better understanding these represents a challenge to optimize the therapeutic use of retinoids. [107,108] Mechanical injury + ± [1,4] Infections ± - [1] Directly associated genetic disorders -+ [3] Risk-associated gene polymorphisms + + [2] Histological features Airspace enlargement + + [1][2][3][4] Elastic fiber destruction/ disrupted assembly + + [37][38][39][40][41] Extracellular matrix remodeling + + [1][2][3][4] Diminished microvasular bed ± + [52][53][54] Dysmorphic capillary vessels + -…”
Section: Relative Inefficiency Of Retinoidsmentioning
confidence: 99%
“…It has been suggested that TFGb1 plays a role in the pathogenesis of chronic SM toxicity (Ghanei and Harandi, 2007;Poursaleh et al, 2012). Generation of reactive oxygen species have been previously shown to influence expression of TFGb1 (Jain et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Other laboratory data to help in developing a prognosis are needed, including DLCO and body plethysmography findings. These issues are discussed by Ghanei et al (2008) and Ghanei & Harandi (2007). (3) It is necessary to interpret the differences in various studies on the level of cytokines.…”
Section: Dear Editormentioning
confidence: 99%